Pharmacy Practice in the South Dakota Correctional System - Chamika Hawkins-Taylor; Angeline M Carlson (University of Minnesota Libraries Publishing, 2018)
Pharmacists must be prepared to care for populations where health disparities are greatest and their services can best impact public health needs. Such preparation requires that students have access to practice experiences in underserved environments where pharmacy practice, cultural competence and knowledge of population health are experienced simultaneously. The correctional facility is such a place. The American Society of Health-System Pharmacists recommends that students receive preceptorship opportunities within the correctional system.  The occasional collaboration or experiential opportunity, like Kingston's early model, has occurred between health professional schools and correctional facilities. However, to date, the correctional facility-experiential site remains an untapped opportunity, at least in a complete, coordinated, pharmaceutical care, patient management framework. Consequently, a short research study asked: To what extent is there potential for correctional facilities to serve as experiential practice sites for pharmacy students? The research objective was to identify pharmaceutical practices within South Dakota correctional system and compare those practices to the guidelines established by the Association of American College of Pharmacy's as optimal for student training. To understand medical and pharmaceutical practices in SDPS, three South Dakota Adult prison facilities were included in the exploratory study.  Data was collected through a mixed methods approach designed to obtain perspectives about the SDPS health care system from individuals representing the numerous job levels and roles that exist within the health care continuum. Interviews and a web-based surveys were used to collect data.  A review of a 36-page transcript along with 498 freeform survey comments revealed that while exact themes from the Exemplary Practice Framework may not have been evident, related words or synonyms for patient-centered care, informatics, public health, medication therapy management, and quality improvement appeared with great frequency.   Article type: Original Research